2023
DOI: 10.1038/s41586-023-06696-z
|View full text |Cite
|
Sign up to set email alerts
|

Targeting myeloid chemotaxis to reverse prostate cancer therapy resistance

Christina Guo,
Adam Sharp,
Bora Gurel
et al.

Abstract: Inflammation is a hallmark of cancer1. In patients with cancer, peripheral blood myeloid expansion, indicated by a high neutrophil-to-lymphocyte ratio, associates with shorter survival and treatment resistance across malignancies and therapeutic modalities2–5. Whether myeloid inflammation drives progression of prostate cancer in humans remain unclear. Here we show that inhibition of myeloid chemotaxis can reduce tumour-elicited myeloid inflammation and reverse therapy resistance in a subset of patients with me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 54 publications
(106 reference statements)
0
17
0
Order By: Relevance
“…The reduction in ANC observed after administration of navarixin was used as an easily monitorable functional biomarker and assumed to be a surrogate for target engagement based on the effect of navarixin in inhibiting the migration of neutrophils (neutrophil trafficking) to the blood [ 25 , 26 ]. A recent study demonstrated a significant positive association between neutrophil count and tumor MDSC infiltration in patients with metastatic CRPC after treatment with another CXCR2 antagonist [ 27 ]. We speculate that the lack of efficacy in our study may be related to the modest ANC reductions (few of which were <0.5 or <1 × 10 9 /L), which may have been insufficient to overcome MDSC activity in the tumor microenvironment and tumor resistance to anti–PD-(L)1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in ANC observed after administration of navarixin was used as an easily monitorable functional biomarker and assumed to be a surrogate for target engagement based on the effect of navarixin in inhibiting the migration of neutrophils (neutrophil trafficking) to the blood [ 25 , 26 ]. A recent study demonstrated a significant positive association between neutrophil count and tumor MDSC infiltration in patients with metastatic CRPC after treatment with another CXCR2 antagonist [ 27 ]. We speculate that the lack of efficacy in our study may be related to the modest ANC reductions (few of which were <0.5 or <1 × 10 9 /L), which may have been insufficient to overcome MDSC activity in the tumor microenvironment and tumor resistance to anti–PD-(L)1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This set of eight genes has been described in late-stage CRPC patient samples, where it correlates with the neutrophil-to-lymphocyte ratio measured from peripheral blood 45 . High blood NLR is associated with shorter survival and treatment resistance 45,48,49 . We detected a four-fold higher correlation between the club cell and high NLR-associated signature scores in the Club region compared to the other epithelial regions ( Figure 3b ).…”
Section: Resultsmentioning
confidence: 99%
“…More generally, tumor sites contain expanded PMN-MDSC populations compared to healthy tissue 72,73 . The success of CXCR2 inhibitors in the treatment of late-stage mCRPC patients proves that castration resistance can be tackled by inhibiting PMN-MDSC function 45 .…”
Section: Discussionmentioning
confidence: 99%
“…AR-pathway independent mechanisms have also been identified, such as combined TP53/RB1 loss driving lineage plasticity from adenocarcinoma to a neuroendocrine phenotype ( 9 , 10 ), autocrine activation via FGFR/MAPK signaling ( 3 ) or IL-6/JAK/STAT signaling ( 4 ), and activation of MAPK signaling via gain-of-function BRAF mutations ( 5 ). Recently, tumor myeloid infiltration has also been demonstrated to mediate resistance to ARSIs in a paracrine fashion, possibly via reactivation of AR signaling, highlighting the role of the tumor microenvironment in resistance development ( 11 ). Of further note, several of the above-mentioned mechanisms may lead to cross-resistance between ARSIs (e.g., enzalutamide and abiraterone) ( 1 ).…”
mentioning
confidence: 99%
“…Metabolic enzymes have been shown to be able to alter chromatin structure via a broad range of epigenetic modifications, to modulate the activity of transcription factors and their coactivators, and to alter mRNA stability, thereby regulating gene expression. Additional roles have been described in cell-cycle progression, homologous recombination repair and non-homologous end joining DNA repair, and in the regulation of a number of key proliferation and survival pathways (i.e., PI3K-AKT-mTOR, MAPK, NF-κB, and TGF-β), as well as in autophagy and apoptosis ( 11 , 25 ). Lastly, noncanonical functions of metabolic enzymes have been implicated in modulation of cytoskeleton dynamics ( 25 ) and remodeling of the tumor microenvironment via exosomes and ectosomes ( 23 ).…”
mentioning
confidence: 99%